2015
DOI: 10.1589/jpts.27.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proprioception training with exercise imagery on balance ability of stroke patients

Abstract: [Purpose] The purpose of the present study was to examine and compare the effects of proprioceptive training accompanied by motor imagery training and general proprioceptive training on the balance of stroke patients. [Subjects and Methods] Thirty-six stroke patients were randomly assigned to either an experimental group of 18 patients or a control group of 18 patients. The experimental group was given motor imagery training for 5 minutes and proprioceptive training for 25 minutes, while the control group was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
0
26
0
3
Order By: Relevance
“…Thus, integrating mental practice into rehabilitation can be expected to enhance its effects. However, most of the information regarding the effects of mental practice is based on studies in which mental practice was performed for periods of several weeks to several months 15 , 16 , 17 ) . Whether limited mental practice can contribute to motor performance improvement in poststroke individuals with hemiparesis is still incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, integrating mental practice into rehabilitation can be expected to enhance its effects. However, most of the information regarding the effects of mental practice is based on studies in which mental practice was performed for periods of several weeks to several months 15 , 16 , 17 ) . Whether limited mental practice can contribute to motor performance improvement in poststroke individuals with hemiparesis is still incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…One made a comparison between motor imagery and real movement by means of cerebrum imaging and showed that both tasks brought about the arrangement of the same neural networks in the premotor cortex, parietal lobe and cerebellum [37], and the other demonstrated that motor imagery training increased dynamic balance ability by activating the neural system [38]. These results propose that the combination of motor imagery training and proprioception program resulted in activation of the cerebellum and cerebrum which in turn affected proprioception, and the visual and vestibular organs responsible for balance ability, especially, that the activation of the proprioception responsible for detecting the position and movements of joints affects the balance ability [39].…”
Section: Discussionmentioning
confidence: 84%
“…Das vinte referências, onze foram avaliados quanto à qualidade (Tabela 1). Dentre as referências com qualidade avaliada, seis estudos não apresentaram boa qualidade metodológica, sendo três transversais [13][14][15] e três ensaios clínicos randomizados [16][17][18] . A Tabela 1 permitiu observar que a maioria dos artigos utilizou delineamento observacional transversal (65%), sendo encontrados ainda cinco ensaios clínicos randomizados (25%) e uma minoria de estudos de caráter mais descritivo (10%).…”
Section: Resultsunclassified
“…Nesta revisão, os estudos que não utilizaram controles para definir parâmetros de simetria tenderam a adotar a tradicional ideia de que o suporte de peso de pessoas com hemiparesia crônica é caracterizado pela distribuição assimétrica com sobrecarga no hemicorpo não-parético. Essa ideia também é predominante na literatura científica que trata do assunto [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]37 .…”
Section: Discussionunclassified